Tailoring Functional Graphene-Derived Geopolymer Nanocomposites: Interfacial Interactions and Mechanical Strength Enhancement - Rathee, Manali; Surendran, Harikrishnan K; Thakur, Aditya; Narayana, Chandrabhas; Lo, Rabindranath; Misra, Anurag; Jayaramulu, Kolleboyina (ACS materials Au, 2025)
Geopolymers are emerging as sustainable alternatives to Ordinary Portland Cement (OPC), offering high strength, lightweight properties, and a lower environmental impact, making them promising materials for green concrete technologies. In this study, we synthesized graphene-based geopolymer nanocomposites using various functional graphene derivatives, such as graphene oxide (GO), sulfonated graphene oxide (G-SO3H) thiographene (G-SH), and phosphate graphene (G-PO3H), along with alumina- and silica-rich waste materials, such as fly ash and dolomite, to enhance mechanical properties, including setting time, flowability, compressive strength, and water absorption. The functional groups on graphene derivatives improve the particle dispersion and matrix density, enhancing compressive strength, while Raman spectroscopy reveals spectral shifts at interfaces of phosphate graphene with dolomite and fly ash, indicating interactions. The resultant FDGP exhibits a significantly higher compressive strength of 45.60 MPa at 7 days and 50.20 MPa at 28 days compared to GO, G-SH, and G-SO3H. The high concentration of phosphate functional groups promotes strong interactions with the geopolymer matrix, improving its workability. Furthermore, density functional theory (DFT) calculations elucidate the role of functional groups in graphene-based geopolymer concrete, enhancing molecular interactions and promoting robust interfacial adhesion with the geopolymer matrix for a superior performance. We studied the time-dependent interactions of functionalized graphene oxide phosphate using DFT and other characterization methods, revealing strong hydrogen bonding that enhances dispersion and reinforcement within the geopolymer matrix.
Keywords: compressive strength; interfacial chemistry; fly ash (FA); geopolymers; functional graphene derivatives; density functional theory (DFT); water absorption